Phenytoin Induced Truncal Ataxia: Need For TDM - jagarlamudi, Anup; Begum, Asma; Saba, Nazmeen; Teegala, Mahalakshmi (Indian Journal of Pharmacy Practice)
Phenytoin is a hydantoin derivative with a narrow therapeutic index and is indicated in GTCS, nonepileptic seizures, status epilepticus, neuritic pain, as skeletal muscle relaxant, ventricular arrhythmias unresponsive to lidocaine or procainamide, arrhythmias induced by cardiac glycosides, and in prophylactic control of seizures during neurosurgery. The usual practice is that phenytoin is given along with other anticonvulsant drugs like benzodiazepines or valproic acid in case of seizures. But this combination of antiepileptic drugs have got serious drug-drug interactions which usually results in exaggerated effects of either of the drugs. A female patient of 24 years admitted with seizures was put on phenytoin, lorazepam, and valproic acid. After a few days of therapy, she had 2 more episodes of seizures and later on developed nystagmus and truncal ataxia. Even though the effects were attributed to "drug", the physicians failed to take necessary action. Lack of a protocol for monitoring plasma concentrations of the narrow therapeutic index drug was responsible for the toxic effects of Phenytoin and by conducting TDM for phenytoin, such toxic effects could have been avoided.
Keywords: Phenytoin; Narrow therapeutic index; Seizures; Truncal ataxia; Nystagmus; Plasma concentrations